Anmeldelser - Tvarnø Lind, Tore (Danish Yearbook of Musicology, 2010)
Review of: Benjamin D. Koen (ed.), with Jacqueline Lloyd, Gregory Barz, and Karen Brummel-Smith (co-eds.): The Oxford Handbook of Medical Ethnomusicology. Oxford and New York: Oxford University Press, 2008.